Community Libraries and Information Centres for Poverty Alleviation in Rural Nigeria - Okite, Maxwell O. (MiddleBelt Journal of Library and Information Science, 2014)
The aim of this paper is to bring to the fore, the role of the rural community library in poverty alleviation in Nigeria. Poverty is a condition whereby individuals do not earn enough income to satisfy the basic necessities of life – food, shelter and clothing. Relying on the available literature, three types of poverty are given as; cyclical, collective and case poverty. The causes of poverty in rural Nigeria among other factors include lack of information infrastructure such as libraries, information centres and public telephony. The effects of poverty are hunger and diseases, high rate of child and infant mortality , prostitution, increase in organised crimes, rural urban migration and, food insecurity, just to mention few. The roles of the community library in rural poverty alleviation includes such services as reference and information services, information packaging, computer training and online business learning support, special job search services to the unemployed and, as an enlightenment centre for the populace. The paper concludes that rural community library is a critical factor in rural poverty alleviation and suggests that governments at all levels should evolve a vibrant rural community library services programme.